Sedition, Securitization, Sexuality: A Conversation between Rohit De and Inderpal Grewal - Inderpal Grewal; Rohit De (South Asia Multidisciplinary Academic Journal)
In this article, Inderpal Grewal and Rohit De discuss the history of the application of India’s law against sedition in relation to questions of sexuality and gender. The conversation between them frames the project of modernity and the state in each of these two scholars’ work, and the ways in which questions of modernity intersect those of “national” and “anti-national” subjectivation. Here, they are interested in how modernity has been formulated in relation to nations, nationalism and commensurate reform movements, and how critiquing these relationships is so deeply informed by feminist scholarship on South Asia, by feminist scholarship on race and ethnicity in the US, and the critique of empire in all of these bodies of work.